KEKERASAN SEKSUAL PADA TOKOH UTAMA GRACE ADAMS DALAM NOVEL MALICE KARYA DANIELLE STEEL - Putu Diah Kanserina (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2011)
Danielle Steel takes the theme of violence in her title novel Malice. The result of this violence makes the main character get traumatism. Representation of the violence in this novel becomes the main topic of research and discussion of this thesis. Two problem formulations which are discussed in this thesis are; (1) how the main character Grace Adams gets the violence in Malice are (2) how the impact of the violence for the main character Grace Adams are. Whereas the approach used in this thesis research is psychoanalysis and structuralism, that is character analysis as fundamental to analyze the violence on the main character Grace Adams, while psychoanalysis to analyze the impact of the violence for the main character Grace Adams. The result of this research indicates that Grace Adams get seduce on her adolescent who her father makes. Grace can afford her problems in her life by using the ego defenses mechanism that are, refusal, isolation, sublimation, and repression.